A Skin-Inspired Self-Adaptive System for Temperature Control During Dynamic Wound Healing - Geng, Yaqi; Chen, Guoyin; Cao, Ran; Dai, Hongmei; Hu, Zexu; Yu, Senlong; Wang, Le; Zhu, Liping; Xiang, Hengxue; Zhu, Meifang (Nano-Micro Letters, 2024)
The thermoregulating function of skin that is capable of maintaining body temperature within a thermostatic state is critical. However, patients suffering from skin damage are struggling with the surrounding scene and situational awareness. Here, we report an interactive self-regulation electronic system by mimicking the human thermos-reception system. The skin-inspired self-adaptive system is composed of two highly sensitive thermistors (thermal-response composite materials), and a low-power temperature control unit (Laser-induced graphene array). The biomimetic skin can realize self-adjusting in the range of 35–42 °C, which is around physiological temperature. This thermoregulation system also contributed to skin barrier formation and wound healing. Across wound models, the treatment group healed 10% more rapidly compared with the control group, and showed reduced inflammation, thus enhancing skin tissue regeneration. The skin-inspired self-adaptive system holds substantial promise for next-generation robotic and medical devices. Highlights: 1 An interactive electronic system inspired by the temperature self-regulation of human skin. 2 Heat stimulation therapy and temperature monitoring during dynamic wound healing. 3 Mechanism of temperature self-regulation during dynamic wound healing.